TEKNO-KULTUR-RELIGI DI ERA REVOLUSI INDUSTRI 4.0: (Studi Netnografi pada Pengguna Aplikasi Muslim Pro di Kalangan Mahasiswa Institut Teknologi Bandung) - Qoriah A Siregar; Dody S. Truna; Dadang Kahmad (Jurnal Sosioteknologi, 2020)
ITB students who use Muslim Pro application on their smartphones as a representation of digital society are a tangible form of techno-cultural-religious interrelationships. ITB students, if they need something related to Islamic religious knowledge and daily worship practices, only need to access the application. Analyzed from the perspective of religious studies, the dynamics and phenomena of techno-culture-religion are an interesting and important entity to study, because the religious activities of ITB students using the Muslim Pro application will have implications and polarization on their religious thought. The main objective of this research is to reveal the religious thoughts of the Muslim Pro application users among ITB students. This research is a qualitative research using netnographic research method (virtual ethnography) based on the theory of religious experience in the form of thought from Joachim Wach. The results of this research indicate that the religious thought patterns of ITB students who use the Muslim Pro application are classified into three types of thought, namely: scientific, literate, and contextual.